STUDI TENTANG LAND REFORM DALAM PERSPEKTIF REFORMASI HUKUM AGRARIA - Hairani, Hairani (Jurnal Cakrawala Hukum, 2017)
To implement agrarian law which was healthy and fair for all people in Indonesia, and also for agriculturedevelopment to improve people welfare, especially farmers who had narrow land or even those who did nothave land, needed to do agrarian reform. The concept was through land reform program. The success oflandreform program implementation depended much on the economic and political system of the governmentholding the power at that time, and on the commitment of the government to do it continuously. Thus, thepolicies issued would support the implementation of land reform program. The purpose of land reform wastoincrease the degree of life and the nation welfare. It became the purpose of agrarian reform law.